Production of Biodegradable Straw from Banana Peel - I Putu Karang Adisurya; Mohammad Affan Fajar Falah (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2022)
This study aims to determine the effect of enhancement in stirring temperature (75oC, 80oC, 85oC) and type of plasticizer (glycerol and sorbitol) on the characteristics of biodegradable straw from ambon banana peel waste and to compare them with the characteristics of conventional boba’s straws. Methods used in this study were tensile strength, elongation, biodegradation, and water uptake tests. The result showed enhancement of stirring temperature and type of plasticizer did not significantly affect the characteristics of biodegradable straws from ambon banana peel waste (p > 0.05). Enhancement of stirring temperature will increase the tensile strength and water resistance value, but decreased elongation and biodegradation value because enhancement of stirring temperature will decrease the water content and increase the molecular density. In addition, plasticizer will increase elongation value and level of biodegradation, but decrease tensile strength and water resistance values. Plasticizer has the ability to increase the elasticity of polymers, as well as increase water absorption because it has hydrophilic hydroxyl groups. Biodegradable straw that have been developed has a colour of black, being rigid, with a length of 13 cm and an external diameter of 1.2 cm. The colour and external diameter of biodegradable boba’s straw looks similar with conventional boba’s straw but shorter in length. Therefore, ambon banana peel waste was promising to be used as an alternative material for biodegradable straw in the future.